Total and heterotrophic soil respiration in a swamp forest and oil palm plantations on peat in Central Kalimantan, Indonesia - Hergoualc'h, Kristell; Hendry, Dede T.; Murdiyarso, Daniel; Verchot, Louis V. (Springer, 2017)
Heterotrophic respiration is a major component of the soil C balance however we critically lack understanding of its variation upon conversion of peat swamp forests in tropical areas. Our research focused on a primary peat swamp forest and two oil palm plantations aged 1 (OP2012) and 6 years (OP2007). Total and heterotrophic soil respiration were monitored over 13 months in paired control and trenched plots. Spatial variability was taken into account by differentiating hummocks from hollows in the forest; close to palm from far from palm positions in the plantations. Annual total soil respiration was the highest in the oldest plantation (13.8 ± 0.3 Mg C ha−1 year−1) followed by the forest and youngest plantation (12.9 ± 0.3 and 11.7 ± 0.4 Mg C ha−1 year−1, respectively). In contrast, the contribution of heterotrophic to total respiration and annual heterotrophic respiration were lower in the forest (55.1 ± 2.8%; 7.1 ± 0.4 Mg C ha−1 year−1) than in the plantations (82.5 ± 5.8 and 61.0 ± 2.3%; 9.6 ± 0.8 and 8.4 ± 0.3 Mg C ha−1 year−1 in the OP2012 and OP2007, respectively). The use of total soil respiration rates measured far from palms as an indicator of heterotrophic respiration, as proposed in the literature, overestimates peat and litter mineralization by around 21%. Preliminary budget estimates suggest that over the monitoring period, the peat was a net C source in all land uses; C loss in the plantations was more than twice the loss observed in the forest.